Glucocorticoid-Induced alterations in DNA methylation in the H19 promoter of Bone Marrow-Derived Mesenchymal Stem Cells are associated with the pathogenesis of osteonecrosis - Song Gong; Lizhi Han; Yang Wang; Yong Feng; Ruoyu Wang; Shizhan Zhang; Kun Nie; Bo Wang; Fei Du; Jianzhong Guan; Lu Zhang; Jiangtao Liu; et al. (PLoS ONE, 2026)
Background Glucocorticoid (GC)-induced osteonecrosis of the femoral head (ONFH) involves bone marrow-derived mesenchymal stem cell (BMSC) apoptosis and dysregulated osteo-adipogenic differentiation. While aberrant H19 promoter methylation and expression have been linked to various bone metabolic disorders such as osteoporosis and osteosarcoma, their specific role in the pathogenesis of GC-induced ONFH remains largely unexplored. Methods We analyzed H19 promoter methylation, DNMTs , and H19 expression in human ONFH BMSCs. Roles of Dnmt1 and H19 in osteogenic/adipogenic differentiation were assessed using staining (Alizarin Red/Oil Red O) and pathway analysis. Effects of Dnmt1 knockdown or H19 overexpression were tested via BMSC implantation in a GC-induced ONFH rat model. Results H19 promoter hypomethylation caused H19 overexpression in undifferentiated GC-ONFH BMSCs; expression decreased upon differentiation. H19 and Dnmt1 expression were negatively correlated. Dnmt1 predominated among DNMTs in epigenetically regulating H19 and reciprocally modulated differentiation (inhibiting osteogenesis, promoting adipogenesis). Conversely, H19 promoted osteogenesis and inhibited adipogenesis by suppressing GSK-3β , activating Wnt/β-catenin signaling. In the rat model, implanted BMSCs with Dnmt1 knockdown or H19 overexpression reduced empty lacunae, corrected the osteo-adipogenic imbalance, and delayed progression. Conclusion The Dnmt1 / H19 / GSK-3β axis reciprocally regulates BMSC osteogenic and adipogenic differentiation in GC-induced ONFH, representing a novel epigenetic mechanism underlying GC-induced ONFH and a promising MSC-based therapeutic strategy for early-stage disease.